Does Eating Out Cause in Overweight and Obesity in Adolescence? - Reny Rahmawati; Ida Nurwati; Budiyanti Wiboworini (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Overweight and obesity, among others, arise from not choosing food intake properly. It was triggered by a shift in people-trend which prefer to buy food outside than at home, mainly during college period. Student food choices that are characterized by high energy, fat, salt, and low fiber can impact on fat accumulation and overweight. The study aimed to explore the association between eating out with overweight and obesity among college student at Sebelas Maret University, Surakarta. This study used a cross-sectional design. As many as 206 respondents were taken using convenience sampling. Data was collected through Google Forms, height and weight were measured based on independent reports and presented descriptively. The relationship between eating out habits and obesity was analized using Chi Square. The prevalence of overweight and obesity among college students was 11.2% and 52.4%, respectively. There was a relationship between eating out habits purchased directly with overweight and obesity in Sebelas Maret University students (p 0,047). Eating out can increase the risk of overweight/obesity in college students. It is necessary to pay attention to the selection of types of food consumed by students outside the home.